Annual Plan of Work and Budget (POWB) for 2021 - CGIAR Research Program on Forests, Trees and Agroforestry (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
The CGIAR Research Program on Forests, Trees and Agroforestry’s (FTA) Plan of Work and Budget (POWB), approved by the Independent Steering Committee (ISC) of FTA and endorsed by the Board of Trustees of FTA’s lead center the Center for International Forestry Research (CIFOR), details the expected key results, planning for effectiveness and efficiency, and program management for 2021.